Association between osteoarthritis and cognitive function: results from the NHANES 2011–2014 and Mendelian randomization study - Kun Zhao; Liuyan Nie; Jingting Zhao; Yankai Dong; Kaixiu Jin; Song Wang; Xiangming Ye (Therapeutic Advances in Musculoskeletal Disease)
Background: Previous meta-analyses have demonstrated osteoarthritis (OA) is associated with an increased risk of dementia, but these studies were prone to bias based on residual confounding factors and reverse causality. Objectives: We aimed to investigate associations between OA and cognitive function using data from the National Health and Nutrition Examination Survey (NHANES) and to investigate the causality using Mendelian randomization (MR). Design: This is a cross-sectional study and MR study. Methods: Data from the NHANES 2011–2014 were used. Multiple linear, logistic regressions and stratified analyses were used to determine the association between OA status and cognitive function. Sample weights were used to ensure result generalizability. Two-sample MR analysis was conducted to examine the association between OA and dementia. Mediation analyses were performed to investigate the mediating effects of depression. Results: We did not demonstrate a significant association between OA and cognitive performance after adjusting for relevant covariates ( p > 0.05), and the population of individuals with both OA and depression was associated with higher odds of low total word recall cognitive performance (odds ratio (OR) = 4.74, 95% confidence interval (CI): 1.09–20.63; p = 0.04). Genetically predicted specific-site OA was not significantly associated with the risk of dementia (OR = 1.12; 95% CI: 0.96–1.32; p = 0.16), Alzheimer’s disease (OR = 0.95, 95% CI: 0.68–1.31, p = 0.74), vascular dementia (OR = 1.32, 95% CI: 0.82–2.13, p = 0.25) with accepted heterogeneity and no evidence of directional pleiotropy. Furthermore, major depression was found to mediate the pathway between OA and vascular dementia (β = 0.044, 95% CI: −0.391 to 0.479, p < 0.05). Conclusion: Our findings indicate that there is no significant association or causal relationship between OA and cognitive decline. However, depression may serve as an important factor influencing cognitive outcomes. Future research should further explore the bidirectional causal relationship and underlying mechanisms.